Model Pemasaran Pendidikan Berbasis Pesantren Dalam Membentuk Citra Baik Madrasah - Moh. Rofiki; Kikik Windiasari; Muhammad Ainul Yaqin (Politeknik Kampar, 2023)
Educational institutions really need educational marketing for sustainability and building a good image. This research wants to explore the educational marketing model of pesantren-based educational institutions in building the good image of madrasas. The research location was at the Fatimatuzzahro madrasah Islamic boarding school Nurul Jadid. The research approach used is qualitative with a case study type. Collecting research data using participant observation techniques, in-depth interviews, and documentation studies. Data analysis is used by reducing data, displaying data and drawing conclusions. The results of the study show that the educational marketing model is carried out through alumni, digital, kyai figures, and word of mouth. This research is expected to have a significant impact on Islamic boarding schools-based educational institutions in carrying out educational marketing in building the good image of madrasah.